STUDI PEMANFAATAN INFORMASI LAPORAN REALISASI ANGGARAN DI LINGKUNGAN PEMERINTAH DAERAH PROVINSI JAWA TENGAH - Alfita Rakhmayani; Sudarno Sudarno (Diponegoro Journal of Accounting, 2014)
Budget report presents an overview of sources, allocation and use of economic resources managed by the government. Understanding and utilization of government information in the financial statements is critical to making an economic decision. This study aims to examine specifically the effect of user characteristics on utilization of budget report. Data were collected through questionnaire distributed to local government agencies in the province of Central Java. Statistical tests were performed using regression analysis. The results showed that experience, gender, level and background of education significantly influence the utilization of budget report information. While social factors did not significantly influence the utilization of budget report information.